Incidence of verbal commentaries on musicians’ corporality during a chamber music rehearsal - Milomes, Luciana Rosario (2018)
Embodied music cognition theory emphasizes the fundamental role of the human body in cognition, and postulates that music is perceived as moving sonic forms that produce corporal resonances through which it is assigned meaning (Leman, 2008). Intersubjectivity refers to the ability to elaborate representations about the mental states of others, allowing us to interpret features of their subjectivity. Joint musical interpretation in rehearsal situations can be understood as an intersubjective process of constructing meaning, which is manifested through various aspects of musical production, during which verbal commentaries play an important role in the formation of joint musical ideas that can be reflected in the musicians’ corporality.